The impact of armed conflict on maternal morbidity and mortality at a teaching hospital in the Tigray region of Ethiopia: a pre-war and wartime comparative analysis - Hale Teka; Mohamedawel Mohamedniguss Ebrahim; Rahel Nardos; Awol Yemane Legesse; Yibrah Berhe; Haileselassie Berhe; Mulugeta Gebregziabher; Gebre-Egziabher Kiros (BMC Pregnancy and Childbirth)
Abstract Background Armed conflict profoundly impacts health systems, access to care, and patient outcomes. In war zones, maternal and neonatal health care is often interrupted, resulting in delayed care, shortages of essential supplies, and compromised quality of care. The war between November 2020 and 2022, the siege on Tigray, and the destruction of infrastructure, including health facilities, have caused massive deaths, morbidity, and the displacement of millions of people. This study examines changes in severe maternal outcomes before and during an armed conflict at the Ayder Comprehensive Specialized Hospital in the Tigray region of Ethiopia. Methods We conducted a retrospective comparative analysis of pre-war vs. wartime analysis of maternal morbidity and mortality among parturient mothers at Ayder Comprehensive Specialized Hospital, Tigray, Ethiopia. Pregnant women or those who are within 42 days postpartum/any form of pregnancy termination that satisfies the WHO Near-miss criteria were enrolled. We compared outcome of women with potentially life-threatening complications from a pre-war period (N = 691) and wartime (N = 428). EpiData 4.6 was used for data entry, and STATA 16.1 and R 4.2.0 were used for analysis. Categorical variables were described using frequencies and percentages, and differences in proportions were tested using chi-square or Fisher’s exact tests. Key indicators of severe maternal outcomes and patterns of organ dysfunction and critical interventions were examined. Results More than half (55%) of the study participants with potentially life-threatening obstetric condition were referred from rural setting during the prewar period as compared to just 9% during the wartime (p<0.001). During the war, the incidences of severe preeclampsia significantly increased from 36.6 to 47.9% (p < 0.001), obstructed labour from 2.0 to 4.4% (p = 0.020), and ICU admissions among mothers with potentially life-threatening complications from 3.5 to 6.1% (p = 0.041). Among women with severe maternal outcomes (i.e., women with maternal near-miss and maternal death), coagulopathy increased significantly (8.8% vs. 63.9%, p < 0.001) and multiple organ dysfunction increased (52.4% vs. 68.3%, p = 0.002). The severe maternal outcome ratio (i.e., maternal near miss + maternal death per 1000 livebirths) increased from 33.2 to 42.7 per 1000 live births (p = 0.013), while the maternal near-miss ratio increased from 28.5 to 39.0 per 1000 live births (p = 0.003). The use of essential interventions, such as oxytocin to prevent postpartum haemorrhage and magnesium sulphate for eclampsia, decreased significantly. Although there was no statistically significant change in the maternal mortality index related to hypertensive disorders (from 37.5% prewar to 61.1% wartime, p = 0.130), mortality associated with haemorrhage (from 12.5% prewar to 61.1% wartime, p = < 0.001) and infectious complications ( from 20.8% prewar, to 55.6% wartime, p = 0.020) worsened. Conclusion The armed conflict in Tigray resulted in a marked deterioration in maternal outcomes and reduced uptake of key obstetric interventions in Ayder Comprehensive Specialized Hospital. As can be indirectly inferred from WHO’s severe maternal outcome indicators, delayed access to care, limited resources, and disrupted referral pathways contributed to an increase in severe maternal and maternal near-miss complications. The dramatic decrease in patients from rural areas suggests that many seriously ill women never reached ACSH — likely contributing to an underestimation of the true impact on maternal mortality. Strengthening referral systems, and ensuring supply chains for essential medicines with a policy of preventing and mitigating the impact of conflict on health and specifically on maternal health.